Antibiogram of Bacteria Isolated from Roasted Bush Meat and Chicken Samples Sold in Afikpo, Nigeria - A, Dike Uzoma (International Journal of Psychosocial Rehabilitation, 2020)
This study was to determine the antibiogram of bacteria isolated from roasted chicken and bush meat sold in Afikpo North L.G.A. The sampling sites emplored in this study were Afikpo (site 1), Amasiri(site 2), Oziza(site 3), Uwana(site 4), Enohia (site 5). The bacteria isolated from bush meat were Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Klebsiella pnuemoniae, Shigella and Salmonella species while the chicken samples bacteria isolated were Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus fecalis, Proteus vulgaris, P.mirabilis Escherichia coli, Klebsiella pnuemoniae, Shigella and Salmonella species. The chicken samples had more bacteria contamination than the bush meat and this could be due to the moisture content, temperature and pH. Moisture content had a range of 86-95(%) while the bush meat had a moisture content of 83-88(%). The pH on the chicken sample ranged from 6.5-7.7 while the bush meat had a pH value range of 6.8-7.4. The temperature had a range of 30-38(oC), while the bush meat had a temperature range of 33- 54(oC). The different microbial groups were enumerated and for the roasted chicken samples, Total aerobic count had a range of 6.6 x 106- 12.4 x 106 cfu/ml, Total coliform count 5.0x105 – 9.2x105 cfu/ml, total fecal coliform count had a range of 3.0x105 - 4.9x105 cfu/ml, total Salmonella and Shigella count, 1.6x104 - 4.0x104 cfu/ml and total Staphylococal count had a range of 0.8x104-3.6x104 cfu/ml while for the bush meat samples, Total aerobic count was 7.9x105-12.4x106 Cfu/ml, total coliform count 5.8x105 – 8.9x105 Cfu/ml, total fecal coliform count 1.9x105 – 5.5x105 cfu/ml, total Salmonella and Shigella count, 0.8x104 - 4.5x104 cfu/ml and total Staphylococal count had a range of 0.5x104-4.1x104 cfu/ml .there was no significant difference (p<0.05) between the chicken and bush meat samples in the same location but there was a significant difference(p<0.05) between the microbial loads on the chicken and bush meat samples at the 5 different sites. Antimicrobial susceptibility test showed that the gram negative bacteria were more resistant than the gram positive bacteria and the isolates from the chicken were more resistant than the bacteria from the bush meat. Ciprofloxacin and perfloxacin showed the most sensitivity to the bacteria isolated from both samples while most drug they were resistant to were septrin (SXT), Ampicillin (AM) and Septromycin(S). This study therefore show that improper hygienic practices and exposure of roasted chicken and meat popularly sold in Afikpo could pose as a public health threat to the consumers. Keywords- , , , , , ,